2014
DOI: 10.4172/2167-0420.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-level Influences on Delays in Diagnostic Follow-up from Mammography Screening in African-American Women: A Systematic Review

Abstract: Although there has been a steady decrease in breast cancer deaths among all women (pooled data) age 40 to 65 years during the past two decades in the United States, breast cancer deaths remain substantially higher among African-American women than White women (32.4% vs. 23.9%), resulting in an overall lower five-year survival rate (78.4% vs. 91.2%). These differences are primarily due to delays in diagnostic follow-up from mammography screening (MS) (ACS, 2012]. Following the secondary research data methods by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Therefore, it is necessary for health insurance programs to cover the cancer diagnostic examinations and treatment procedures. Moreover, similar to other studies (23,25,26), low education level and low income were risk factors for patient delay. So that more lowincome patients referred to physicians in stage III.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, it is necessary for health insurance programs to cover the cancer diagnostic examinations and treatment procedures. Moreover, similar to other studies (23,25,26), low education level and low income were risk factors for patient delay. So that more lowincome patients referred to physicians in stage III.…”
Section: Discussionsupporting
confidence: 86%
“…Comparison of patients in MUA/MUP designated areas with areas eligible but never designated provides another dimension to existing literature on how community organization may affect service delivery and potentially health outcomes like later stage at diagnosis. 20, 26, 27, 3033 But designation is primarily related to NHBlack and NHWhite disparity and in the end, the primary issues related to disparity in later stage at diagnosis appear to be access to mammography and follow-up at accredited facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have found that, compared to their more affluent counterparts, individuals living in lower SES neighborhoods exhibit maladaptive health behaviors and experience worse health outcomes. 34,35 In a related vein, research has found that accessibility of medical services in the neighborhood is an important factor for missed or delayed use of medical services. 36 , 37 Hypotheses Based on FIT, Andersen's HSU model, and the empirical findings in the literature, we hypothesize that: (1) a mutually affectionate parent-child relationship in early adolescence is inversely related to depressive mood from early adolescence to emerging adulthood; depressive mood is directly related to later cigarette smoking in the 20s-30s; and depressive mood and cigarette smoking are positively associated with physical health problems in early midlife.…”
Section: Enabling Factorsmentioning
confidence: 99%